Linking Serum Vitamin D Deficiency and Menstrual Irregularities in North Karnataka: Insights from a Cross-sectional Study - Lata K. Mankani; V. M. Padamavathi; Udayashree Voorkara; B. B. Annadaneshwari (Annals of African Medicine, 2026)
Abstract Background: Menstrual irregularities are common among young women and may be associated with Vitamin D deficiency, as it may play a role in reproductive and menstrual health. Aim: The aim is to evaluate and compare the serum Vitamin D levels in women with regular and irregular menstrual cycles in a tertiary care hospital in North Karnataka. Materials and Methods: This comparative cross-sectional study was carried out in the Department of Obstetrics and Gynecology, Tertiary Care Teaching Hospital, from March 2025 to February 2026. A total of 150 women aged 18–25 years were enrolled, of which 75 were women with regular menstrual cycles and 75 women with irregular menstrual cycles. Detailed demographic and menstrual history was obtained using a structured pro forma. The serum level of 25-hydroxy Vitamin D (25[OH]D) was classified as deficient (